Reproductive Status Affecting the Incidence of Hypertension in Pregnancy at Prof. Dr. Chairuddin P. Lubis Educational Hospital, Medan City - Luthfiah Mawar; Rahayu Lubis; Asfriyati Asfriyati; M. Agung Rahmadi; Helsa Nasution (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Hypertension in pregnancy is one of the leading causes of maternal mortality, with a global prevalence of 5–10% (Khedagi & Bello, 2021). This study aims to analyze the effect of reproductive status—maternal age, gravidity, and parity—on the incidence of hypertension in pregnancy at Prof. Dr. Chairuddin P. Lubis Educational Hospital, Medan. A case-control design was employed with 96 respondents, consisting of 48 cases and 48 controls. Bivariate analysis revealed that pregnant women aged ≥35 years have a 2.839-fold higher risk of developing hypertension compared to those aged <35 years (OR=2.839; 95% CI: 1.123–7.177; p=0.027). First pregnancy (primigravida) increases the risk by 2.742 times compared to multigravida (OR=2.742; 95% CI: 1.047–7.178; p=0.040), while nulliparous women have a 2.714-fold higher risk compared to those who have given birth (OR=2.714; 95% CI: 1.101–6.693; p=0.030). Multivariate analysis identified maternal age ≥35 years and nulliparity as the most significant predictors (p=0.005). These findings align with studies by Wiranto & Putriningtyas (2021), Hinkosa et al. (2020), and Luo et al. (2020), which confirmed that advanced maternal age and nulliparity increase the risk of pregnancy complications. The novelty of this research lies in integrating all three reproductive status factors as simultaneous predictors of hypertension risk, providing a new perspective compared to previous studies focused on single variables. Based on these findings, early detection and targeted health education for high-risk mothers are strongly recommended.